1982
DOI: 10.2134/jeq1982.00472425001100040018x
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of 2,4‐D and 2,4,5‐T n‐Butyl Esters in Soils Following Massive Application to Field Mini‐Lysimeters

Abstract: Concentrations of 2,4‐dichlorophenoxyacetic acid (2,4‐D) and 2,4,5‐trichlorophenoxyacetic acid (2,4,5‐T) in soils and leachates from field mini‐lysimeters were monitored for up to 28 months to characterize the patterns of herbicide mobility in soils under climatic conditions of the Palouse region of the Pacific Northwest. The lysimeters contained soils from Washington, Wyoming, or Mississippi, and were treated with 1,120 or 5,600 kg/ha of a 1:1 mixture of 2,4‐D and 2,4,5‐T n‐butyl esters in 1976, 1977, or 1978… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In one study, it was found that the maximum content of 2,4-D in water samples of rivers in the western United States sampled in 1968 was 0.35 ppb; 18 ppb of 2,4-D was found in irrigation return flow at Moses Lake, Washington. For drinking water, although the standard treatments in filtration plants reduce unduly high surges down to lower concentrations, they are in adequate to eliminate persistent lowlevel concentrations of 2,4-D. [2] Majka et al [3] reported that dissipation of 2,4-D and 2,4,5-T herbicides in the acidic Mississippi soils were extremely slow even at the lower application rate. Surface soil pH was lowered following herbicides' application.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, it was found that the maximum content of 2,4-D in water samples of rivers in the western United States sampled in 1968 was 0.35 ppb; 18 ppb of 2,4-D was found in irrigation return flow at Moses Lake, Washington. For drinking water, although the standard treatments in filtration plants reduce unduly high surges down to lower concentrations, they are in adequate to eliminate persistent lowlevel concentrations of 2,4-D. [2] Majka et al [3] reported that dissipation of 2,4-D and 2,4,5-T herbicides in the acidic Mississippi soils were extremely slow even at the lower application rate. Surface soil pH was lowered following herbicides' application.…”
Section: Introductionmentioning
confidence: 99%
“…Ricardo et al (1998) reported drifting loss during application of iso-octyl ester of 2,4-D in air. In a study carried out in 1978, it was found that when a 1:1 mixture of 2,4-D and 2,4,5-T (2,4,5 trichloro-phenoxy acetic acid) was applied to a field in Florida at 4,480 kg ha -1 , 54 % of the applied herbicides remained in the soil profile even after 414 days with 37 % being present in the top 15 cm soil layer; when the same was applied to a field in Washington, over 30 ppm was found in leachates (Majka et al, 1982). Toxic hazards caused by many herbicides like atrazine, simazine, 2,4-D, 2,4,5-T, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence has been accumulated to suggest that many water resources of India are polluted with organic pesticides [7,13,16]. 2,4-Dichloro-phenoxy-acetic acid (2,4-D) and 2-chloro-4-ethyalamino-6-isopropylaminos-traiazine (atrazine) are two widely used herbicides in the world as well as India and they were found in surface water and ground water in different countries of the world [3,10,11,12,15].…”
Section: Introductionmentioning
confidence: 99%